The effects of ball possession and won duels for the success ofthe match in the European Football Championship –Euro 2020 - Myftiu, Armend; Berisha, Myftiu (VIREF Revista de Educación Física, 2022)
Aim: the aim of this research is to show the relations, effects, and interactions of ball possession, won duels, and goals scored inside the penalty area in the European Football Championship, Euro 2020. Methods: the research involves 24 final stage teams in the tournament and the above-mentioned relevant factors for the success of the match were analyzed. The percentage of ball possession is divided into three groups (low, medium, and high), the percentage of won duels are divided into two groups (low and high), while all goals scored inside the penalty area are taken into account for the success of the match. Two-way factorial variance analysis ANOVA was used to calculate the main and intercept effects. Findings: ball possession has shown a significant main effect ((F2,18) = 17.60, p < 0.001, ηp2 = 0.66), which means that teams, depending on the percentage of ball possession, showed differences in goals scored within the penalty area. Duel winning has shown no statistically significant main effect ((F1,18) = 2.09, p > 0.16, ηp2 = 0.10). Therefore, the success of scoring goals probably does not depend on the percentage of won duels. Interaction, ball possession and duel winning show statistically significant effects ((F2,18) = 4.16, p < 0.03, ηp2 = 0.31) for the success of the match, respectively goals scored within the penalty area. Discussion: ball possession from a low to a medium percentage is influenced to some extent by won duels in relation to the success of goals scored within the penalty area, while teams with a high percentage of ball possession and a low percentage of won duels managed to achieve a larger number of goals within the penalty area.